(untitled) (Jurnal Adabiya, 2025)
This study aims to improve descriptive text writing skills in grade X students of SMA Negeri 10 Fajar Harapan Banda Aceh through the implementation of the Technological Pedagogical Content Knowledge (T-PACK) learning model utilizing Instagram social media. The background of this study departs from the results of observations and interviews that indicate that writing is the most difficult skill for students to master, especially in the aspects of grammar, word choice, punctuation, and spelling. In addition, monotonous learning and limited use of technology in the school environment cause low student learning motivation. Initial data obtained through formative assessment (pre-test) showed variations in student writing abilities, where 21.8% of students were in the category of needing guidance, 31.3% were sufficient, 37.5% were good, and only 9.4% were very good. The implementation of the T-PACK model was carried out by integrating Instagram as a learning medium. Students were directed to observe examples of descriptive texts, do drafting, write collaboratively, and publish their work on Instagram. This process was followed by presentations and reflections to measure understanding and increase motivation. The results of the study showed that the use of T-PACK-based digital media was able to increase students’ interest, motivation, and learning outcomes in writing descriptive texts. Support from the school, teachers, and active student involvement were important factors in the success of this study. Abstrak Penelitian ini bertujuan untuk meningkatkan keterampilan menulis descriptive text pada siswa kelas X SMA Negeri 10 Fajar Harapan Banda Aceh melalui penerapan model pembelajaran Technological Pedagogical Content Knowledge (T-PACK) dengan memanfaatkan media sosial Instagram. Latar belakang penelitian ini berangkat dari hasil observasi dan wawancara yang menunjukkan bahwa menulis merupakan keterampilan paling sulit dikuasai oleh siswa, terutama dalam aspek tata bahasa, pemilihan kata, tanda baca, dan ejaan. Selain itu, pembelajaran yang monoton dan keterbatasan penggunaan teknologi di lingkungan sekolah menyebabkan rendahnya motivasi belajar siswa. Data awal diperoleh melalui asesmen formatif (pre-test) yang menunjukkan variasi kemampuan menulis siswa, di mana 21,8% siswa berada pada kategori perlu bimbingan, 31,3% cukup, 37,5% baik, dan hanya 9,4% sangat baik. Implementasi model T-PACK dilakukan dengan mengintegrasikan Instagram sebagai media pembelajaran. Siswa diarahkan untuk mengamati contoh teks deskriptif, melakukan drafting, menulis secara kolaboratif, dan mempublikasikan hasil karya mereka di Instagram. Proses ini diikuti dengan presentasi dan refleksi untuk mengukur pemahaman serta meningkatkan motivasi. Hasil penelitian menunjukkan bahwa penggunaan media digital berbasis T-PACK mampu meningkatkan minat, motivasi, dan capaian hasil belajar siswa dalam keterampilan menulis descriptive text. Dukungan dari pihak sekolah, guru, serta keterlibatan aktif siswa menjadi faktor penting dalam keberhasilan penelitian ini